Emotional and cognitive influences in air traffic controller tasks: An investigation using a virtual environment?. (May 2018) - Truschzinski, Martina; Betella, Alberto; Brunnett, Guido; Verschure, Paul F.M.J.
Abstract: Air traffic controllers are required to perform complex tasks which require attention and high precision. This study investigates how the difficulty of such tasks influences emotional states, cognitive workload and task performance. We use quantitative and qualitative measurements, including the recording of pupil dilation and changes in affect using questionnaires. Participants were required to perform a number of air traffic control tasks using the immersive human accessible Virtual Reality space in the "eXperience Induction Machine". Based on the data collected, we developed and validated a model which integrates personality, workload and affective theories. Our results indicate that the difficulty of an air traffic control task has a direct influence on cognitive workload as well as on the self-reported mood; whereas both mood and workload seem to change independently. In addition, we show that personality, in particular neuroticism, affects both mood and performance of the participants. Highlights: Investigation of air controller tasks in a Virtual Environment. Development and validation of cognitive and emotional model. Different task difficulties influence the workload and self-reported mood. Neuroticism affects mood and performance. Mood changes are independent of workload change.